ANALISIS PENDAPATAN PETANI SILVOPASTURA DI DESA AMAN DAMAI, KECAMATAN SIRAPIT, KABUPATEN LANGKAT - Sahroni Lubis; Siti Latifah; Tri Martial (Peronema Forestry Science Journal, 2016)
Forest land use to agriculture recognized cause problems such as decreased soil fertility, erosion, extinction of flora and fauna, floods, droughts and even global environmental change. One land management system to tackle this problem is the model of agroforestry. Silvopastura management in the village of Aman Damai is still underdeveloped, and the lack of research related to land management system with silvopastura. Based on this, the study aims to identify the components of silvopastura, to know silvopastura practice contributes to the household income, and analyze factors that affect the income of silvopastura farmers in the Aman Damai of village. This research was done in May 2015. Sampling was done by purposive and methods used in the form of multiple linear regression analysis. The research showed that Component of silvopastura In Aman Damai village include component (wood plants) in the form of multipurpose tree species (MPTs) with the components of the farm (pasture). Multipurpose tree species that was developed is avocado, star fruit, durian, guava, citrus, cocoa, rubber, kuini, olive, mango, jackfruit, petai, Rambe, rambutan, and sapodilla. While the type of pasture being developed are chickens, goats, buffaloes, and cows. Silvopastura practices contribute to the household income of Rp. 397. 368. 000 (52.56%), greater than the contribution of farming to household income is Rp. 358.800.000 (47, 44%). The independent variables that significantly affect the dependent variable is a variable number of pasture and land ownership. Keywords : Farmers income, Silvopastoral, Multipurpose trees species (MPTS), Aman Damai Village.